Mechanisms of Chondrocyte Survival and Matrix Synthesis During Hypoxia - Pfander, David; Grimmer, Claudia; Muller, Lutz; Aigner, Thomas; Cramer, Thorsten (Current Rheumatology Reviews, 2007)
Growth-plate cartilage and articular cartilage are virtually avascular tissues. Thus, chondrocytes must exist in extreme microenvironmental conditions, most prominently characterized by low oxygen tension. Diffusion distances for oxygen and nutrients between arteries and single chondrocytes range from 50 m to 3mm. Therefore, chondrocytes need specific strategies to adapt to these hostile conditions. Furthermore, they have to synthesize ATP in order to fulfill their main function, i.e. the synthesis of proteoglycans and type II collagen. In recent years increasing evidence for a pivotal role of the transcription factor hypoxia inducible factor-1 (HIF-1α) in cartilaginous tissues has been published. Murine growth-plates with functionally inactivated HIF-1α displayed great defects in their central areas caused by massive cell death. This very important observation points out that HIF-1α is absolutely necessary for chondrocytes to survive developmental hypoxia. Furthermore, it has been shown that HIF-1α has important functions for the regulation of anaerobic energy generation and matrix synthesis. Beside hypoxia, which seems to be more pronounced during osteoarthritis, other factors like pro-inflammatory mediators are able to activate HIF-1α in chondrocytes. Thus, an increasing dependence of OA chondrocytes on the adaptive functions of HIF-1 is reasonable to assume. In this review we will summarize the knowledge about HIF-1α for chondrocyte survival and matrix synthesis of growth-plate and articular cartilage during development and disease.
Keywords: OA